Development of A Web-Based Nearpod Application in Increasing Elementary School Students' Interest in Learning - Andi Chairunnas; Dendy Saeful Zen; Henny Annisa Rahmawati; Mira Mirnawati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Implementing TPACK-based learning in Indonesia is still far from perfect. This is because the habit of implementing the TPACK-based learning process has not yet been formed. The success of the TPACK-based learning process is still greatly influenced by the ability of teachers and students to access technology as a learning support medium. Implementing TPACK-based learning requires media to convey learning information and communication between teachers and students. The research objective of this study is to develop a Web-based Nearpod application to increase student intelligence and interest in elementary school. The development of the web-based Nearpod application has a plan that goes through several stages carried out by researchers based on the ADDIE development model. The first stage was carrying out the analysis. The analysis was carried out at SDIT Putra Pakuan. The researcher prepares the learning media design in the second stage by determining the material to develop and make a storyboard. The third stage is for the researcher to develop a design created using the Nearpod application. The development product is interactive learning media based on the Nearpod theme, how rich my country is, and the sub-theme utilization of natural resources in Indonesia, which contains learning material accompanied by text, images, learning videos, learning simulations, practice questions, educational games, and quizzes. The fourth stage is implementation. The product that has been developed is tested by class IV students to find out the responses of teachers and students after the learning media is installed and applied in class. The fifth stage is evaluation. At this stage, the researcher analyzes the responses of teachers and students after using the development product. The development research results concluded that the development product was successful, as seen from the percentage results, which showed a value of 81%-100% with an interpretation of "Very Good." The results of expert validation and teacher and student responses prove the feasibility of Nearpod-based interactive learning media. The results of experts' validation of learning media were declared very feasible. The validation results from media experts obtained a percentage of 97.33%, which means it is very suitable and can be used without revision. Language experts obtained a percentage of 94.66%, which means it is very suitable for use without revision, and learning material experts obtained a percentage of 98.66%, which means it is very suitable for use without revision. Students' interest in learning consists of understanding the concept of learning material, feeling like they like the learning situation, and feeling like they like learning activities. This can be seen from the students' activeness in class during the learning process.